2015
DOI: 10.1097/ypg.0000000000000097
|View full text |Cite
|
Sign up to set email alerts
|

The Met allele of BDNF Val66Met polymorphism is associated with increased BDNF levels in generalized anxiety disorder

Abstract: These results suggest that BDNF could be involved in the neurobiology of GAD and might represent a useful marker associated with the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…31 In contrast, a significant association between the Met allele and risk for GAD (p = 0.014) has been reported: the Met allele was significantly associated with an increase in serum BDNF levels compared with the Val/Val genotype in GAD participants (p = 0.048). 4 In another study, the Val66Met polymorphism was not associated with GAD and showed no Genetic Polymorphisms and Generalized Anxiety Disorder Alves V M influence on BDNF plasma levels. 25 Few studies have been conducted about serum BDNF as a biomarker in patients with anxiety disorders.…”
Section: ■ Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…31 In contrast, a significant association between the Met allele and risk for GAD (p = 0.014) has been reported: the Met allele was significantly associated with an increase in serum BDNF levels compared with the Val/Val genotype in GAD participants (p = 0.048). 4 In another study, the Val66Met polymorphism was not associated with GAD and showed no Genetic Polymorphisms and Generalized Anxiety Disorder Alves V M influence on BDNF plasma levels. 25 Few studies have been conducted about serum BDNF as a biomarker in patients with anxiety disorders.…”
Section: ■ Resultsmentioning
confidence: 99%
“…The neurobiology of this disorder is still unclear, although it has been consistently shown that environmental and genetic factors may increase the risk. 4 Genetic epidemiology has produced convincing evidence that anxiety and related disorders Genetic Polymorphisms and Generalized Anxiety Disorder Alves V M are influenced by genetic factors and that the genetic component is highly complex, polygenic, and epistatic.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 However, Val66Met variation was associated with neither GAD nor BDNF plasma levels in a Chinese Han population with GAD. 66 In addition, polymorphisms both in regulator of G-protein signaling 2 (RGS2) and neuropeptide Y (NPY) genes have been shown to modify risk of post-disaster GAD under conditions of high stressor exposure among adults living in areas affected by the 2004 Florida Hurricanes 67,68 and few single-nucleotide polymorphisms (SNPs) in proteasome modulator 9 (PSMD9) gene were in linkage with GAD in Italian families with type 2 diabetes.…”
Section: Genetic Biomarkersmentioning
confidence: 96%
“…The BDNF Val66Met SNP has been associated with risk for psychiatric disorders and suicide (Hong et al, 2011). This functional SNP prevents the activity-dependent release of BDNF (Egan et al, 2003) and some – but not all (Moreira et al, 2015; Tramontina et al, 2007) – studies have found that Met-carriers have lower serum BDNF levels (Ozan et al, 2010; Zakharyan and Boyajyan, 2014). …”
Section: Introductionmentioning
confidence: 99%